2018
DOI: 10.15252/emmm.201708613
|View full text |Cite
|
Sign up to set email alerts
|

Cited4 is a sex‐biased mediator of the antidiabetic glitazone response in adipocyte progenitors

Abstract: Most antidiabetic drugs treat disease symptoms rather than adipose tissue dysfunction as a key pathogenic cause in the metabolic syndrome and type 2 diabetes. Pharmacological targeting of adipose tissue through the nuclear receptor PPARg, as exemplified by glitazone treatments, mediates efficacious insulin sensitization. However, a better understanding of the context‐specific PPARg responses is required for the development of novel approaches with reduced side effects. Here, we identified the transcriptional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Liver and muscle triglycerides were extracted as previously described [24] and determined with the Serum Triglyceride Determination Kit (TR0100, Sigma Aldrich, Munich Germany) and the Mithras Microplate Reader (Berthold Technologies GmbH & Co, Germany). Insulin tolerance test (ITT) and glucose tolerance test (GTT) were performed as previously described [25].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver and muscle triglycerides were extracted as previously described [24] and determined with the Serum Triglyceride Determination Kit (TR0100, Sigma Aldrich, Munich Germany) and the Mithras Microplate Reader (Berthold Technologies GmbH & Co, Germany). Insulin tolerance test (ITT) and glucose tolerance test (GTT) were performed as previously described [25].…”
Section: Methodsmentioning
confidence: 99%
“…To isolate progenitor cells for seeding or sorting [25], gWAT was dissected and digested as described previously [29], [30]. The Lin-Sca1+ fraction cells were counted using a hemocytometer and seeded on laminin-coated 24-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The cells in this subcluster demonstrated strong chemokine secretion and the ability to recruit neutrophils. Additionally, we identified CITED4, EPAS1 and PPARG as genes that were more highly expressed in the Adipo-CAR subcluster, which were all closely involved in regulating adipose production 53–56. According to our results, cluster 3 was closely associated with the multidirectional differentiation function of MSCs and increased MSC-C2 was the most stemmed transcription factor cluster (figure 2E).…”
Section: Discussionmentioning
confidence: 66%
“…[ 37 ] Depot, age, and gender specific effects of various other genes has also been reported, for example Cited4 has distinct roles in regulating thermogenic gene expression in female and male mice, and different fat depots. [ 38 ] Previous in vitro studies showed that knockdown of Prmt5 in 3T3‐L1 cells inhibits adipogenic differentiation and adipogenic gene expression, [ 17 ] through a mechanism involving Prmt5 facilitated enhancer–promoter looping to promote expression of Ppar γ 2. [ 18 ] However, we did not observe a very significant decrease in Pparγ expression in Prmt5 ‐null adipocytes.…”
Section: Discussionmentioning
confidence: 99%